Sorção e dessorção do herbicida indaziflam e metabólitos no solo - Alonso, Diego Gonçalves (2012)
The concern with environmental impacts in the soil, water, and its microorganisms caused by pesticides is a current issue, widely discussed between scientists and mainly by agencies that regulate their use. Pesticides persistency and mobility in the environment are directly linked to the potential for contamination since their availability in the soil facilitates processes of leaching, volatilization, runoff, absorption by plants, and degradation. Retention through sorption and desorption processes influences direct or indirectly the other processes and, in turn, is controlled by the interaction among physicochemical characteristics of these molecules and the soil. Due to the relevance of the subject, a series of laboratory experiments was carried out using batch equilibration techniques to determine partitioning coefficients of indaziflam and its metabolites indaziflam-triazinediamine (FDAT), indaziflam-triazine-indanone (ITI), and indaziflam-carboxilic acid (ICA) in soils with different physicochemical characteristics. The effect of incubation time in the process of sorption of indaziflam and the metabolite FDAT was studied for two different depths of a Brazilian soil. Partitioning coefficient values (Kd and Koc) of indaziflam and its metabolites determined in six Brazilian soils and three American soils showed higher sorption for the parent compound and sequentially for the metabolites ITI, ICA, and FDAT. Freundlich coefficients (Kf and Kf,oc) were estimated for all soils and Kf normalization for organic carbon contents reduced soil sorption variability in all cases. Kf values of indaziflam and its metabolites ITI and ICA correlated significantly with organic carbon contents of all soils, while Kf values for FDAT did not correlate with any physicochemical characteristics of the soils studied. Mobility classification of chemical compounds in the soils demonstrated that indaziflam and ITI are considered moderately mobile, ICA shows higher variability, from mobile to moderately mobile, and FDAT is mobile. Desorption was hysteretic for all compounds and soils. Incubation time promoted the increase in Kd values for indaziflam and FDAT with significant increase in the first two weeks. However, the effect of time in Kd values was not enough to alter the mobility classification of these compounds.